Innovative HR Mastery: Crafting Cool Kids Start-Up Excellence - Princess Meira Shyiang Sri; Uun Lestari; Soraya Ramadani; Yusni Kristen; Tawakkal Tawakkal (Trescode Green Organization, 2024)
This study aims to describe the application of Human Resource Management in recruiting employees to improve performance at the Cool Kids start up business at the Panakukkang Makassar Mall, analysis of Human Resource Management in HR development efforts to improve employee performance at the Cool Kids start up business, HRM analysis has an impact on recruitment as well as efforts in developing human resources to improve employee performance in the Cool Kids start up field at the Panakukkang Makassar Mall. In this study using the type of field research or field research. This study uses a descriptive qualitative approach. This research approach was carried out at Cool Kids in Panakukkan Makassar Mall with data collection techniques in the form of interviews, observation, documentation and accommodation methods. The results of this study are expected that the recruitment system carried out by Cool Kids at Panakukkan Makassar Mall is not fully maximized, so using the human resource management recruitment model can be carried out effectively. In an effort to develop Cool Kids' human resources at the Panakukkang Makassar Mall, this has been carried out in accordance with the procedures for implementing employee education and training programs, but this has not yet been implemented informally. HR development and recruitment have an impact on improving employee performance at Cool Kids which has not been fully implemented, this is due to the knowledge, abilities and skills of employees not all of them can master them effectively.